Peningkatan Literasi Perbankan Siswa Sekolah Menengah Pertama (SMP): Bank Mempermudah Transaksi Kita - Kery Utami; Masripah Masripah (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2020)
It is undeniable that banking transactions are already inherent in everyday life. Therefore, banking literacy needs to be owned by each individual. People who are well literate easier to understand matters related to banking and have information to access the necessary banking services. To support efforts to improve financial literacy, one of which is in the banking sector, socialization in the form of community service needs to be done. Community service is intended for young junior high school students (SMP-IT ARAFAH, Depok) with the theme